2020
DOI: 10.1002/jctb.6570
|View full text |Cite
|
Sign up to set email alerts
|

Development of a continuous‐flow anaerobic co‐digestion process of olive mill wastewater and municipal sewage sludge

Abstract: BACKGROUNDOlive mill wastewater (OMW) represents an environmental problem due to its high organic load and relevant concentration of phenolic compounds (PCs). OMW treatment and disposal represents a relevant challenge and cost for olive mills and multi‐utilities in charge of waste management in Mediterranean countries. The goal of this study was to develop an anaerobic co‐digestion (co‐AD) process of OMW and sewage sludge (SwS) from municipal wastewater treatment.RESULTSDifferent volumetric OMW:SwS ratios up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In contrast with the results presented here, they yielded higher amounts of biogas and methane with lower quantities of OMWW. Bovina et al [ 51 ] reported an increase in biogas and methane yield with the increasing of OMWW content instead of sewage sludge, obtaining the best performances with 25% OMWW (with 1.01 ± 40 g.L −1 of polyphenols)—i.e., 116 NL.kg VS –1 of methane. Calabrò et al [ 52 ] used raw and concentrated OMWW with polyphenols values ranging between 1.1 ± 0.12 and 4.4 ± 0.03 g.L −1 in order to obtain up to 2 g.L −1 PPs in the blends they tested in batch under mesophilic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with the results presented here, they yielded higher amounts of biogas and methane with lower quantities of OMWW. Bovina et al [ 51 ] reported an increase in biogas and methane yield with the increasing of OMWW content instead of sewage sludge, obtaining the best performances with 25% OMWW (with 1.01 ± 40 g.L −1 of polyphenols)—i.e., 116 NL.kg VS –1 of methane. Calabrò et al [ 52 ] used raw and concentrated OMWW with polyphenols values ranging between 1.1 ± 0.12 and 4.4 ± 0.03 g.L −1 in order to obtain up to 2 g.L −1 PPs in the blends they tested in batch under mesophilic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies often focus on improving final yields without taking into account the use of energy resources, which is a key aspect when scaling up a process. It is therefore essential to ensure a quantification of the energy use in each technology to balance the associated costs and efficiency (Bovina et al, 2021). Consequently, the assessment of the energy cost of bioenergy utilization has been the subject of intensive research in recent years (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…ALP use as a substrate for biogas production by WAD has been extensively studied on a laboratory scale (Borja et al, 1993; Boubaker & Cheikh Ridha, 2007; Bovina et al, 2021; Roig et al, 2006), but when the bioprocess is carried out on a larger scale, the high production costs and dependence on water make it an unsustainable alternative. Moreover, ALP contains 98% of the polyphenolic compounds ( PhC ) present in the olive fruit, a content that varies depending on the olive variety, the ripening of the stone fruit, the oil extraction system used and the storage time after extraction (Carmona et al, 2023; Solomakou & Goula, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is extremely important to safely handle such materials [1,2]. It is estimated that one ton of olives is responsible for producing 0.6 tons of olive mill solid residue [3,4]. Olive pits (OP) are residues that form part of the solid wastes produced by the olive oil manufacturing industry during the processing and extraction of olive oil from olives [5,6].…”
Section: Introductionmentioning
confidence: 99%